2015
DOI: 10.1001/jamaoncol.2015.0245
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Exposure to Thiopurines and Risk of Relapse in Children With Acute Lymphoblastic Leukemia

Abstract: Importance Variability in prescribed 6-mercaptopurine and lack of adherence to 6-mercaptopurine could result in intra-individual variability in systemic exposure to 6-mercaptopurine (measured as erythrocyte thioguanine nucleotide levels) in children with acute lymphoblastic leukemia. The impact of intra-individual variability in systemic exposure to 6-mercaptopurine on relapse risk is unknown. Objective To determine impact of high intra-individual variability in 6-mercaptopurine systemic exposure on relapse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(167 citation statements)
references
References 28 publications
5
157
2
2
Order By: Relevance
“…Although the participation rate of study participants across the 87 participating institutions is not available, we have previously shown that the AALL03N1 study participants were comparable to patients enrolled on the relevant parent COG therapeutic first-line ALL protocols. 15 Only patients who had both evaluable MEMS and self-report data were included in this analysis.…”
Section: Study Participantsmentioning
confidence: 99%
“…Although the participation rate of study participants across the 87 participating institutions is not available, we have previously shown that the AALL03N1 study participants were comparable to patients enrolled on the relevant parent COG therapeutic first-line ALL protocols. 15 Only patients who had both evaluable MEMS and self-report data were included in this analysis.…”
Section: Study Participantsmentioning
confidence: 99%
“…These include inferior geographic access to care, 3 insurance, 3 tolerance of therapy, 4 and treatment adherence. 5 There appear to be biological differences in some histologically similar malignancies presenting in pediatric, AYA, and older patients. 6 In addition, there likely are substantial developmental differences in pharmacokinetics/pharmacodynamics that influence toxicity and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Anyway, the CACE approach was used to estimate the true effect in the presence of noncompliance. 32 The current EFS results do not support the routine use of cyclophosphamide and methotrexate as metronomic agents after standard chemotherapy for nonmetastatic OST. Compliance is a major concern when one considers cancer treatments and more specifically long-term treatments.…”
Section: Discussionmentioning
confidence: 60%